Determinants of stock returns based on fundamental approach : evidence from finance sector of Bursa Malaysia / Suzanne Albert - Albert, Suzanne (2016)
Fundamental analysis involves the use of financial statement in predicting the stock return. Present study aims whether the accounting measure or historical accounting data or more known as fundamental analysis able to predict the future earnings of the companies or investors. The purpose of this study is to identify whether the fundamental analysis able to predict the stock returns for companies listed in Bursa Malaysia based on the stock price movements. This study used three fundamental areas; profitability, leverage and market value ratio to predict the stock returns. This study used three ratio under the three areas which is ROA, DR and MBR for the profitability ratio, leverage ratio and market value ratio respectively. Data were selected from the period of 2004 until 2014. The sample of the study consists of the companies listed in Bursa Malaysia under the finance sector. OLS regression were used to conduct the study and the study found that fundamental analysis have negative and insignificant impact in predicting the stock returns.